Method and device for manufacturing high-purity quartz sand by liquid phase discharge method
Through the purification method of liquid discharge method, the solution of quartz sand solves the problem of poor effects when removing aluminum, titanium, lithium and other elements, and realizes the efficient purification and high purity of high -pure quartz sand.
Patent Information
- Application Number
- CN202411505958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing quartz sand purification method is not ideal when removing metal elements such as aluminum, titanium, and lithium. Moreover, the tiny metal salt ions formed by these impurities during acid and alkali leaching are difficult to completely clean, affecting the purity of high-purity quartz sand.
The liquid discharge method is used to remove the surface metal impurities by pre -treatment, and then placed it in an electrolytic battery of the alkaline electrolyte, and the pulse DC voltage is applied to purify the liquid discharge. This method includes multiple steps: pre -processing, purifying liquid discharge, neutralization, dehydration, and dehydroxy, and eventually obtained high pure quartz sand.
This method can effectively remove metal elements such as aluminum, titanium, and lithium in quartz sand, improve the purity of quartz sand, and make it not easy to absorb tiny particles on the surface.
Smart Images

Figure CN119370851A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz sand purification methods, and in particular to a method and a device for manufacturing high-purity quartz sand by a liquid phase discharge method. Background Art
[0002] High-purity quartz sand refers to quartz sand with a silicon dioxide content greater than 99.99%. It can be used in photovoltaic new energy, national defense and military industry, electronic semiconductors and other fields. It is an industrial raw material with strategic significance.
[0003] At present, the purification treatment of quartz sand on the market is mainly carried out through chemical processes such as acid leaching and alkali leaching. For details, please refer to the following documents. The Chinese invention patent application document with application publication number CN112919478A discloses a method for preparing high-purity quartz, including the following steps: alkali leaching: mixing the quartz ore after screening with sodium hydroxide solution for hot leaching; acid leaching: mixing the quartz after alkali leaching with hydrochloric acid solution for hot leaching, and then washing, filtering and drying to obtain high-purity quartz. The Chinese invention patent with authorization announcement number CN 114477188 B discloses a method for purifying high-purity quartz sand, including the following operations: soaking quartz sand with a chemical solution, the chemical solution includes acid and / or alkali solution, and separating and removing the chemical solution after soaking; soaking quartz sand with silica colloid, and separating and removing silica colloid after soaking; obtaining purified quartz sand.
[0004] The acid leaching and alkali leaching processes for quartz sand purification can achieve good removal effects on copper, iron, calcium and other elements in quartz sand, but the removal effect on metal elements such as aluminum, titanium and lithium is not ideal. This is because the content of these impurity elements themselves is low, they mostly exist in inclusions, and they are easy to form impurities in the lattice; on the other hand, during the acid leaching and alkali leaching processes, smaller metal salt ions will be generated. These metal salt ions are easily adsorbed on the surface of quartz sand particles and cannot be cleaned by conventional ultrasonic oscillation water washing methods, thereby affecting the purity of high-purity quartz sand. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for producing high-purity quartz sand by liquid phase discharge method, wherein the surface of the prepared high-purity quartz sand is not easy to adsorb tiny particles, has high purity, and has good removal effect on metal elements such as aluminum, titanium, and lithium.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions: A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following method steps:
[0007] Step S1, pretreatment, the quartz sand is magnetically separated and then placed in a mixed acid treatment solution and soaked for 6-8 hours, and then taken out and washed with ultrapure water to obtain pretreated sand;
[0008] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; inserting a cathode connected to the negative pole of the power supply into the electrolytic cell, inserting an anode connected to the positive pole of the power supply into the reaction container, turning on the power supply, applying a pulsed DC voltage of 15-45V to the electrolytic cell, and removing the quartz sand in the reaction container after treating for 30-120 minutes for standby use;
[0009] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into the combined acid neutralization solution and immersing for 30 to 60 minutes, then taking it out and washing it with ultrapure water;
[0010] Step S4, dehydration, adding a coupling agent to the quartz sand treated in step S3 and mixing them evenly, and then removing the water contained in the quartz sand by centrifugal dehydration;
[0011] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950-1050° C. for 30-50 minutes to obtain the high-purity quartz sand.
[0012] Through the above technical scheme, the surface of quartz sand is first corroded by mixed acid to remove metal impurities on the surface of quartz sand that are easy to react with acid, and then the quartz sand is placed in an electrolytic cell of alkaline electrolyte, and the impurities on the quartz sand are further corroded and stripped by alkaline electrolyte. Under the action of pulse voltage, a large number of hydrogen bubbles are formed on the surface of the anode in the electrolytic cell, and then a bubble layer is formed to wrap the anode, so that the alkaline electrolyte and the anode are insulated in a short time, and a potential gradient is generated to form an electric field. When the field strength exceeds the critical value, an electric shock occurs, that is, the bubble layer is broken down, and spark discharge is generated. The high temperature generated by the spark discharge acts on the surface of the quartz sand, and the impurities on the surface of the quartz sand are peeled off by thermal stress, and cracks are generated on the surface of the quartz sand, so that the impurities inside the quartz sand can be better etched; the impurities and metal ions peeled off from the quartz sand have a particle size much smaller than the particle size of the quartz sand. Under the combined effect of charge, gravity and water flow, they pass through the filter holes of the reaction container, and large particles gradually settle at the bottom of the electrolytic cell, and small metal cations are attracted and gathered near the cathode, so that the surface of the quartz sand is not easy to adsorb small particles; after completing the liquid phase discharge purification of the quartz sand, the quartz sand is immersed in a combined acid neutralizing solution, which, on the one hand, neutralizes the alkali solution remaining on the surface of the quartz sand, and on the other hand, further etches and purifies the quartz sand through the cracks generated on the surface of the quartz sand during the liquid phase discharge purification process.
[0013] Preferably, in step S2, a pressure nozzle is provided at the lower part of the anode, and water flow is impacted on the quartz sand near the discharge end of the anode by the pressure nozzle, so that the quartz sand generates tumbling flow.
[0014] Through the above technical solution, the water flow sprayed by the pressure nozzle impacts the quartz sand, causing the quartz sand to tumble and flow, so that the quartz sand can receive the discharge stripping effect of the anode more evenly and efficiently.
[0015] Preferably, the pressure nozzle is connected to a circulating water pump, and the alkaline electrolyte at the cathode is pumped to the vicinity of the anode by the circulating water pump.
[0016] Through the above technical scheme, as the anode discharges, the alkaline electrolyte in the alkaline electrolyte reacts with the impurities in the quartz sand, so that the concentration of the alkaline electrolyte near the anode is lower, and the alkaline electrolyte at the cathode is pumped to the anode through the action of the circulating water pump, so that during the discharge process, the alkaline electrolyte near the anode is maintained in a relatively constant concentration range.
[0017] Preferably, the mixed acid treatment solution comprises 3-5wt% HF, 0-2wt% H 2 SO 4 , 8-14 wt% HCl and 0.5-1 wt% hydroxyethylidene diphosphonic acid.
[0018] Through the above technical solution, the HF in the mixed acid treatment solution can effectively corrode the surface of the quartz sand, and then on the newly exposed surface, H 2 SO 4 and HCl can efficiently react with metal impurities such as Fe, Ca, Mg, and Al to generate metal salt ions; hydroxyethylidene diphosphonic acid can form complexes with various metal ions such as iron, copper, aluminum, and zinc, and play a role in precipitation and conversion in acid solutions. 2 SO 4 The corrosiveness is strong, but the concentration is relatively low, so the reaction finally generates chloride salts and complexes with high solubility. At the same time, hydroxyethylidene diphosphonic acid plays a film-forming role on the surface of quartz sand in the subsequent liquid phase discharge purification process, thereby buffering the liquid phase discharge process, reducing excessive removal, balancing chemical corrosion and discharge removal processes, and thus achieving a better purification effect on quartz sand.
[0019] Preferably, the alkaline electrolyte comprises 7-10 wt % NaOH, 14-20 wt % KOH and 2-5 wt % sodium dodecyl sulfate.
[0020] Through the above technical solution, the degree of ionization of KOH is higher than that of NaOH, and its alkalinity is stronger. -If the concentration is too low, its corrosiveness is too weak; if it is too high, more insoluble precipitates will be formed. By mixing NaOH and KOH, the ionized OH in the solution during the discharge process will be - It always maintains a relatively constant concentration range, so that it can have a good discharge purification effect on quartz sand; sodium dodecyl sulfate, as a surfactant, improves the surface wettability of the anode, reduces the surface tension, significantly reduces the thickness of the gas layer, and reduces the critical voltage of liquid phase discharge, thereby improving the removal efficiency and achieving the purpose of purification.
[0021] Preferably, the combined acid neutralization solution includes 0.5-1 wt % hydrochloric acid and 0.5-1 wt % oxalic acid.
[0022] Through the above technical scheme, hydrochloric acid is used as a pH regulator to neutralize the alkaline solution and adjust the pH of the solution. Oxalic acid provides oxalate ions as a ligand for metal ion complexes to convert certain slightly soluble precipitates formed in an alkaline environment into soluble chelates.
[0023] Preferably, the coupling agent is a silane coupling agent.
[0024] Through the above technical solution, the hydrophilic end of the silane coupling agent is connected with the OH group on the surface of the quartz sand. - The hydrophobic end faces outward, forming a monomolecular layer on the surface of the quartz sand, which reduces the surface energy of the quartz sand, reduces the ability of the particles to adsorb impurities and micropowder in the air, and reduces the tendency of the particles to attract each other, thereby being able to dehydrate the quartz sand better and effectively reduce the adsorption of tiny particles by the quartz sand.
[0025] Preferably, the cathode is a plate-type graphite electrode, and the anode is a tungsten rod electrode with a tapered end.
[0026] Through the above technical scheme, graphite has good corrosion resistance to most acids, alkalis and organic solvents, and the plate structure has a large contact area with the alkaline electrolyte, which has a good discharge effect; tungsten has good chemical stability and has good corrosion resistance to most acids, alkalis and organic solvents. By setting its end into a cone, its discharge effect is further enhanced.
[0027] Another object of the present invention is to provide a device for producing high-purity quartz sand by liquid phase discharge method. The surface of the prepared high-purity quartz sand is not easy to adsorb tiny particles, has high purity, and has good removal effect on metal elements such as aluminum, titanium, and lithium.
[0028] A device for manufacturing high-purity quartz sand by liquid phase discharge method comprises an electrolytic cell, a reaction vessel and a direct current pulse power supply, wherein the electrolytic cell is filled with alkaline electrolyte; the reaction vessel is provided with filter holes, a plate-type graphite electrode is provided at one end inside the electrolytic cell, the plate-type graphite electrode is connected to the negative electrode of the direct current pulse power supply, a tungsten rod electrode is provided inside the reaction vessel, and the tungsten rod electrode is connected to the positive electrode of the direct current pulse power supply.
[0029] Through the above technical scheme, when the device for manufacturing high-purity quartz sand by liquid phase discharge method is used to discharge and purify quartz sand, the quartz sand is placed in a reaction container, and then the reaction container is placed in an electrolytic cell, so that the alkaline electrolyte immerses the quartz sand in the reaction container, and then the plate graphite electrode and the tungsten rod electrode are respectively connected to the negative electrode and the positive electrode of the DC pulse power supply. Through pulse discharge, a large number of hydrogen bubbles are formed on the surface of the tungsten rod electrode, and then a bubble layer is formed to wrap the anode, so that the alkaline electrolyte and the anode are insulated in a short time, and a potential gradient is generated to form an electric field. When the field strength exceeds a critical value, a Electric shock, that is, breaking through the bubble layer, produces spark discharge. The high temperature generated instantly by the spark discharge acts on the surface of the quartz sand, and the impurities on the surface of the quartz sand are peeled off by thermal stress, and cracks are generated on the surface of the quartz sand, so that the impurities inside the quartz sand can be better etched; the impurities and metal ions peeled off from the quartz sand have a particle size much smaller than the particle size of the quartz sand. Under the combined effect of charge, gravity and water flow, they pass through the filter holes of the reaction container, and large particles are gradually deposited at the bottom of the electrolytic cell, and small metal cations are attracted and gathered near the cathode, making it difficult for the surface of the quartz sand to adsorb small particles.
[0030] Preferably, it also includes a circulation component, which includes a circulating water pump, a water inlet pipe connected to the water inlet end of the circulating water pump, and a water outlet pipe connected to the water outlet end of the circulating water pump; a pressure nozzle is arranged at the lower part of the tungsten rod electrode, and the water outlet pipe of the circulating water pump is connected to the pressure nozzle.
[0031] Through the above technical scheme, as the anode discharges, the alkaline electrolyte in the alkaline electrolyte reacts with the impurities in the quartz sand, so that the concentration of the alkaline electrolyte near the anode is lower. By setting a circulation component, when the quartz sand is electrochemically purified, the water inlet pipe is close to one end of the plate graphite electrode, and the electrolyte at the plate graphite electrode is pumped to the tungsten rod electrode through a circulating water pump, so that during the discharge process, the alkaline electrolyte near the anode is maintained in a relatively constant concentration range. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which constitute a part of the specification, illustrate embodiments of the present invention and, together with the description, serve to explain the principles of the present invention.
[0033] Figure 1 It is a scanning electron microscope image of the high-purity quartz sand samples of Examples 1-6.
[0034] Figure 2 It is the scanning electron microscope image of the quartz sand sample of comparative example 1-2.
[0035] Figure 3 It is a structural schematic diagram of Example 7.
[0036] In the figure, 1. electrolytic cell; 2. reaction container; 3. DC pulse power supply; 4. plate graphite electrode; 5. alkaline electrolyte; 6. tungsten rod electrode; 7. circulation component; 71. circulation water pump; 72. water inlet pipe; 73. water outlet pipe; 74. nozzle connector; 8. pressure nozzle. DETAILED DESCRIPTION
[0037] In order to more clearly illustrate the present invention, the invention is further described in detail below in conjunction with the embodiments. It should be understood by those skilled in the art that the following description is an explanation of the invention content, not a limitation, and therefore, the protection scope of the present invention should not be limited thereto.
[0038] Example
[0039] Example 1
[0040] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0041] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, after being taken out, it is washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 3wt% HF, 8% HCl and 0.5wt% hydroxyethylidene diphosphonic acid.
[0042] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 7wt% NaOH, 14wt% KOH and 2wt% sodium dodecyl sulfate.
[0043] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 15V to the electrolytic cell, and after processing for 30 minutes, remove the quartz sand in the reaction container for use.
[0044] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0045] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0046] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950° C. for 30 minutes to obtain the high-purity quartz sand.
[0047] Example 2
[0048] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0049] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, taken out, and washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 5wt% HF, 2wt% H 2 SO 4 , 14% HCl and 1 wt% hydroxyethylidene diphosphonic acid.
[0050] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 7wt% NaOH, 14wt% KOH and 2wt% sodium dodecyl sulfate.
[0051] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 15V to the electrolytic cell, and after processing for 30 minutes, remove the quartz sand in the reaction container for use.
[0052] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0053] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0054] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950° C. for 30 minutes to obtain the high-purity quartz sand.
[0055] Example 3
[0056] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0057] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, after being taken out, it is washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 3wt% HF, 8% HCl and 0.5wt% hydroxyethylidene diphosphonic acid.
[0058] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 10wt% NaOH, 20wt% KOH and 5wt% sodium dodecyl sulfate.
[0059] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 15V to the electrolytic cell, and after processing for 30 minutes, remove the quartz sand in the reaction container for use.
[0060] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0061] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0062] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950° C. for 30 minutes to obtain the high-purity quartz sand.
[0063] Example 4
[0064] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0065] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, after being taken out, it is washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 3wt% HF, 8% HCl and 0.5wt% hydroxyethylidene diphosphonic acid.
[0066] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 7wt% NaOH, 14wt% KOH and 2wt% sodium dodecyl sulfate.
[0067] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 45V to the electrolytic cell, and after processing for 30 minutes, remove the quartz sand in the reaction container for use.
[0068] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0069] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0070] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950° C. for 30 minutes to obtain the high-purity quartz sand.
[0071] Example 5
[0072] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0073] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, after being taken out, it is washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 3wt% HF, 8% HCl and 0.5wt% hydroxyethylidene diphosphonic acid.
[0074] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 7wt% NaOH, 14wt% KOH and 2wt% sodium dodecyl sulfate.
[0075] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 15V to the electrolytic cell, and after treating for 120 minutes, remove the quartz sand in the reaction container for use.
[0076] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0077] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0078] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950° C. for 30 minutes to obtain the high-purity quartz sand.
[0079] Example 6
[0080] A method for producing high-purity quartz sand by liquid phase discharge method, comprising the following steps:
[0081] Step S1, pretreatment, quartz sand after magnetic separation is placed in a mixed acid treatment solution and soaked for 6 hours, after being taken out, it is washed with ultrapure water to obtain pretreated sand; the mixed acid treatment solution includes 3wt% HF, 8% HCl and 0.5wt% hydroxyethylidene diphosphonic acid.
[0082] Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; the alkaline electrolyte includes 7wt% NaOH, 14wt% KOH and 2wt% sodium dodecyl sulfate.
[0083] Insert a cathode connected to the negative pole of the power supply into the electrolytic cell, insert an anode connected to the positive pole of the power supply into the reaction container, turn on the power supply, apply a pulsed DC voltage of 15V to the electrolytic cell, and after treating for 120 minutes, remove the quartz sand in the reaction container for use.
[0084] Step S3, neutralization treatment, adding the quartz sand treated in step S2 into a combined acid neutralization solution and immersing for 30 minutes, then taking it out and washing it with ultrapure water; the combined acid neutralization solution includes 0.5wt% hydrochloric acid and 0.5wt% oxalic acid.
[0085] Step S4, dehydration, adding a silane coupling agent to the quartz sand treated in step S3, and then centrifugally dehydrating at a speed of 800-1200 rpm.
[0086] Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 1050° C. for 30 minutes to obtain the high-purity quartz sand.
[0087] Example 7
[0088] A device for producing high-purity quartz sand by liquid phase discharge method, hereinafter referred to as purification device, Figure 3 , including an electrolytic cell 1, a reaction container 2, a DC pulse power supply 3 and a circulation component 7. The electrolytic cell 1 contains an alkaline electrolyte 5; a plate-type graphite electrode 4 is arranged at one end of the electrolytic cell 1, and the plate-type graphite electrode 4 is connected to the negative electrode of the DC pulse power supply 3.
[0089] The reaction container 2 is made of an inert material that is not easy to react with the alkaline electrolyte 5, and is provided with a filter hole. A tungsten rod electrode 6 is provided inside the reaction container 2, and a pressure nozzle 8 is provided on the reaction container 2 below the tungsten rod electrode 6.
[0090] The bottom of one end of the electrolytic cell 1 away from the plate graphite electrode 4 is provided with a nozzle joint 74 for connecting and docking with the pressure nozzle 8. The circulation assembly 7 includes a circulating water pump 71, a water inlet pipe 72 connected to the water inlet end of the circulating water pump 71, and a water outlet pipe 73 connected to the water outlet end of the circulating water pump 71; the water outlet pipe 73 is connected to the nozzle joint 74.
[0091] When using the purification device to purify quartz sand by liquid phase discharge, the quartz sand is placed in the reaction container 2, and then the reaction container 2 is placed in the electrolytic cell 1, so that the nozzle connector 74 is connected to the pressure nozzle 8 at the bottom of the reaction container 2. The alkaline electrolyte 5 in the electrolytic cell 1 should be able to immerse the quartz sand in the reaction container 2. The tungsten rod electrode 6 is connected to the positive electrode of the DC pulse power supply 3, the DC pulse power supply 3 is turned on, and the circulating water pump 71 is started.
[0092] Comparative Example
[0093] Comparative Example 1
[0094] A method for preparing high-purity quartz comprises the following steps:
[0095] Alkali leaching: The quartz ore after screening is mixed with sodium hydroxide solution for hot leaching. The alkali leaching conditions are alkali concentration of 0.06 mol / L and addition rate of 5 ml (g·min) -1 , temperature is 300℃, leaching time is 4 hours;
[0096] Acid leaching: The quartz leached with alkali solution is mixed with hydrochloric acid solution for hot leaching. The acid leaching conditions are acid concentration of 0.06 mol / L and addition rate of 5 ml (g·min) -1 , the temperature is 300℃, the leaching time is 4 hours, and then it is washed, filtered and dried to obtain high-purity quartz.
[0097] The above method and process section is taken from the patent application document with application publication number CN112919478A, entitled A method and device for purifying high-purity quartz sand.
[0098] Comparative Example 2
[0099] A method for purifying high-purity quartz sand comprises the following steps:
[0100] (1) Quartz sand raw material: The vein quartz ore was pre-treated by crushing, calcining, water quenching and grinding to obtain quartz sand raw material with a particle size of 100 mesh. The quartz sand raw material was heated by microwave with a heating power of 2000 W and a heating time of 1 h.
[0101] (2) Mixed acid leaching: Soak the quartz sand in a chemical solution. The chemical solution is a mixture of 20% sulfuric acid, 20% hydrochloric acid, and 10% hydrofluoric acid. The leaching temperature is 80°C and the leaching time is 4 hours.
[0102] (3) Purification of silica colloid: quartz sand is soaked in silica colloid, the silica colloid used is ultra-high purity silica colloid with a purity of 99.9999% and a mass concentration of 20%. The silica colloid is first subjected to an alternating current field (10V / 20kHz) for 5 minutes to fully contact with the quartz sand, then allowed to stand for 30 minutes, and then separated from the quartz sand by a direct current field (100V).
[0103] (4) Clean and dry the quartz sand.
[0104] The above method and process section is taken from the patent document with authorization announcement number CN 114477188 B, entitled A method and device for purifying high-purity quartz sand.
[0105] Test methods
[0106] The quartz sand samples prepared in Examples 1-6 and the quartz sand samples prepared in Comparative Examples 1-2 were tested according to the following method.
[0107] 1. The quartz sand sample was tested for impurity elements according to the method in JY / T 0567-2020. The test results are shown in Table 1.
[0108] 2. The quartz sand samples of Examples 1-6 and Comparative Examples 1-2 were observed under an electron microscope, using a JSM-IT510 electron microscope with a magnification of 500.
[0109] Figure 1 In the figure, numbers 1-6 correspond to the electron microscope images of the quartz sand samples of Examples 1-6 respectively.
[0110] Figure 2In the figure, numbers 7-8 correspond to the electron microscope images of the quartz sand samples of Examples 1-2, respectively.
[0111]
[0112] Table 1 Detection results of impurity content of quartz sand samples
[0113] It can be seen from Table 1 that Examples 1-6 are significantly better than Comparative Examples 1-2 in removing the three impurities of Al, Li and Ti; and are also better than Comparative Examples 1 and 2 in terms of overall impurity content.
[0114] Judging from the results of the embodiments, appropriately increasing the concentration of the mixed acid treatment solution and the alkaline electrolyte or increasing the dehydroxylation heating temperature has a certain promoting effect on impurity removal; simply increasing the pulse power supply voltage or extending the liquid phase discharge reaction time cannot significantly improve the impurity removal effect, but will affect the overall removal effect due to excessive removal.
[0115] From Table 1 and Figure 1 , Figure 2 It can be seen from the electron microscope photos that the technical effect achieved by the technical means provided by the present invention is superior to the traditional mixed acid washing, alkali washing or silica colloidal purification method in terms of overall removal amount and treatment of the three difficult-to-remove elements of aluminum, lithium and titanium. The technical method provided by the present invention has a good removal effect on the main impurity elements in quartz sand, and the surface of quartz sand is smooth and not easy to absorb tiny particles. After being treated by this method, the quartz sand raw material can reach the standard of high-purity quartz sand.
[0116] Although some specific embodiments of the invention have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the invention. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the invention. The scope of the invention is defined by the appended claims.
Claims
1. A method for producing high-purity quartz sand by liquid phase discharge method, characterized in that: The method comprises the following steps: Step S1, pretreatment, the quartz sand is magnetically separated and then placed in a mixed acid treatment solution and soaked for 6-8 hours, and then taken out and washed with ultrapure water to obtain pretreated sand; Step S2, liquid phase discharge purification, placing the pretreated sand into a reaction container of insulating material, the reaction container is provided with filter holes, the diameter of the filter holes is smaller than the diameter of the selected quartz sand; placing the reaction container into an electrolytic cell filled with alkaline electrolyte, so that the alkaline electrolyte immerses the pretreated quartz sand in the reaction container; inserting a cathode connected to the negative pole of the power supply into the electrolytic cell, inserting an anode connected to the positive pole of the power supply into the reaction container, turning on the power supply, applying a pulsed DC voltage of 15-45V to the electrolytic cell, and removing the quartz sand in the reaction container after treating for 30-120 minutes for standby use; Step S3, neutralization treatment, adding the quartz sand treated in step S2 into the combined acid neutralization solution and immersing for 30 to 60 minutes, then taking it out and washing it with ultrapure water; Step S4, dehydration, adding a coupling agent to the quartz sand treated in step S3 and mixing them evenly, and then removing the water contained in the quartz sand by centrifugal dehydration; Step S5, dehydroxylation, heating the quartz sand treated in step S4 at 950-1050° C. for 30-50 minutes to obtain the high-purity quartz sand.
2. The method for producing high-purity quartz sand by a liquid phase discharge method according to claim 1, characterized in that: In step S2, a pressure nozzle is arranged at the lower part of the anode, and the quartz sand near the discharge end of the anode is impacted by the pressure nozzle to make the quartz sand tumble and flow.
3. The method for producing high-purity quartz sand by a liquid phase discharge method according to claim 2, characterized in that: The pressure nozzle is connected to a circulating water pump, and the alkaline electrolyte at the cathode is pumped to the vicinity of the anode through the circulating water pump.
4. The method for producing high-purity quartz sand by a liquid phase discharge method according to claim 1, characterized in that: The mixed acid treatment solution includes 3-5wt% HF, 0-2wt% H2SO4, 8-14wt% HCl and 0.5-1wt% hydroxyethylidene diphosphonic acid.
5. The method for producing high-purity quartz sand by liquid phase discharge method according to claim 1, characterized in that: The alkaline electrolyte includes 7-10 wt % of NaOH, 14-20 wt % of KOH and 2-5 wt % of sodium dodecyl sulfate.
6. The method for producing high-purity quartz sand by a liquid phase discharge method according to claim 1, characterized in that: The combined acid neutralization solution includes 0.5-1 wt % of hydrochloric acid and 0.5-1 wt % of oxalic acid.
7. The method for producing high-purity quartz sand by liquid phase discharge method according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
8. The method for producing high-purity quartz sand by liquid phase discharge method according to claim 1, characterized in that: The cathode is a plate-type graphite electrode, and the anode is a tungsten rod electrode with a conical end.
9. A device for producing high-purity quartz sand by liquid phase discharge method, characterized in that: It includes an electrolytic cell, a reaction container and a DC pulse power supply. The electrolytic cell is filled with alkaline electrolyte. The reaction container is provided with a filter hole. A plate-type graphite electrode is provided at one end of the electrolytic cell. The plate-type graphite electrode is connected to the negative electrode of the DC pulse power supply. A tungsten rod electrode is provided inside the reaction container. The tungsten rod electrode is connected to the positive electrode of the DC pulse power supply.
10. The device for producing high-purity quartz sand by liquid phase discharge method according to claim 9, characterized in that: It also includes a circulation component, which includes a circulation water pump, a water inlet pipe connected to the water inlet end of the circulation water pump, and a water outlet pipe connected to the water outlet end of the circulation water pump; a pressure nozzle is arranged at the lower part of the tungsten rod electrode, and the water outlet pipe of the circulation water pump is connected to the pressure nozzle.
Citation Information
Patent Citations
Preparation method of high-purity quartz
CN112919478A
A method and apparatus for purifying high-purity quartz sand
CN114477188B
Method for preparing high-purity silicon by high temperature gas-solid reaction
CN101481111A
Polycrystalline silicon preparation method
CN103101912A
Continuous smelting method and equipment for silica powder produced from diamond wire cutting
CN109052408A